Account of compliance of precast disk of overlapping in the calculation of frames - Trekin Nikolay; Bybka Alexander (E3S Web of Conferences, 2023)
The article provides a description of the methodology for taking into account pliable interfaces of prefabricated reinforced concrete disks of floors of multi-storey frame buildings when modeling by the finite element method. The results of numerical studies and a comparative analysis of numerical studies of the compliance of the floor disk with experimental data are presented. The results of the study of the effect of compliant interaction of structures on the stress-strain state of a multi-storey frame are shown.